Pengembangan Lembar Kerja Peserta Didik Berbasis Discovery Learning dengan Pendekatan Saintifik pada Materi Struktur dan Fungsi Tumbuhan - Anggarwati, Melania Gisella; Ningsih, Kurnia; Titin (Jurnal Ilmiah Edukatif, 2024)
The purpose of this study is to develop and evaluate the efficacy of the student worksheet based on discovery learning and a scientific approach to the material structure and function of plants. The employed research method is Borg and Gall development research, which consists of five stages: research and information gathering, planning, product development, product testing, and product revision. The instruments for research were LKPD validation sheets and multiple-choice tests. CVR and CVI values of 1.00 indicated that discovery-based learning worksheets with a scientific approach were valid and suitable for use as instructional materials. Based on the results of the effect size test calculation, a student worksheet based on discovery learning and a scientific approach developed has an effectiveness value of 3.60 in the strong category. This demonstrates the use of discovery-based learning worksheets with a scientific approach contributing 99.98% of the learning outcomes of 34 students in class VIII E at SMPN 14 Pontianak regarding the structure and function of plants